Effects of dietary L-Carnitine and DDGS on growth, carcass characteristics, and loin and fat quality of growing-finishing pigs - Ying, W.; Tokach, Michael D.; Dritz, Steven S.; Houser, Terry A.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 1,104 barrows and gilts (PIC 337 × 1050, initially 80 lb) were used in a 109-d study to evaluate the effects of dietary L-Carnitine and dried distillers grains with solubles (DDGS) on growth, carcass traits, and loin and fat quality. Pigs were blocked by weight and randomly assigned to 1 of 6 treatments with 7 replications per treatment. Treatments were arranged as a 2 × 3 factorial with main effects of added DDGS (0 or 30% in Phases 1, 2, and 3 and 20% in Phase 4) and L-Carnitine (0, 50, or 100 ppm). Dietary treatments were corn-soybean meal-based and fed in 4 phases. Overall (d 0 to 109), dietary L-Carnitine improved (P < 0.02) ADG, which resulted in greater (P < 0.02) final BW with the response tending to be linear (P < 0.07). For F/G, a DDGS × L-Carnitine interaction (quadratic, P < 0.01) was observed. This was the result of pigs fed 50 ppm L-Carnitine, with no DDGS having better F/G than pigs fed 0 or 100 ppm, but in diets containing DDGS, pigs fed 50 ppm L-Carnitine had worse F/G compared with those fed 0 or 100 ppm. In carcass traits, pigs fed dietary L-Carnitine had greater (P < 0.02) HCW compared with those not fed dietary L-Carnitine. Also, increasing dietary L-Carnitine increased carcass weight (quadratic, P < 0.03), carcass yield (quadratic, P < 0.07), and backfat (quadratic, P < 0.04), with the maximum response observed from pigs fed 50 ppm dietary L-Carnitine. In loin quality, feeding dietary L-Carnitine increased (P < 0.04) purge loss compared with pigs fed no L-Carnitine, with the response being linear (P < 0.03). In jowl fat fatty acid profile, as expected, feeding dietary DDGS increased (P < 0.001) Linoleic acid, total polyunsaturated fatty acids (PUFA), the ratio of unsatu- rated fatty acids to saturated fatty acids, and iodine value (IV) compared with feeding no dietary DDGS; however, feeding L-Carnitine did not alter jowl fatty acid composi- tion. Feeding dietary L-Carnitine improved ADG and carcass weight, with the maximal response observed at 50 ppm, but dietary L-Carnitine did not affect loin or fat quality.
Keywords: Swine; carcass characteristics; DDGS; Fatty acid; Iodine value; L-Carnitine; Loin